Influence of Electrolyzed Oxidizing Water (EOV) on the Preservation of Strawberry (Fragaria × ananassa Duch.) Fruit Quality - UNUK, TATJANA; BAŠKOVČ, TANJA; VIDMAR, GAJ; VOGRIN, ANDREJ; TOJNKO, NINA (Anali PAZU, 2026)
Strawberry is a highly perishable fruit crop, prompting growers to seek methods for improving its postharvest storage potential during cultivation. The aim of this study was to evaluate the effect of electrolyzed oxidative water (EOW) on the microbial and physiological stabilization of strawberry fruits and their sensory quality. The experiment was conducted in an organic plantation of the 'Clery' cultivar, where two application methods (spraying and fruit dipping) and two EOW concentrations (4% and 8%) were tested. The results showed that the gender and age of the assessors significantly influenced sensory evaluations, whereas a single EOW application did not significantly improve fruit storage performance. Storage temperature was confirmed as the primary factor affecting microbial activity and postharvest preservation.
Keywords: strawberry; storage; microbial activity; quality; sensorial evaluation